ANALISA TINGKAT LAYANAN JALAN MENGGUNAKAN METODE STANDAR PELAYANAN MINIMAL (SPM) - Refiyanni, Meidia; Silvia, Cut Suciatina (Universitas Teuku Umar, 2019)
Road service assessments need to be carried out periodically both structurally and non-structurally. The minimum servant standard (SPM) of the road is a measure of the road that must be implemented by the government that the road can be operated in accordance with the standards mandated by government regulations. The purpose of this research was to find out the level of service performance of the road network in Suak Indrapuri - Lapang and to see road connectivity in Johan Pahlawan District, West Aceh. The evaluation results on the three road routes in Johan Pahlawan District showed that the accomplishment of SPM from accessibility aspects on route I was 0.148, route II was 0.133 and on route III 0.140 ?that it show did not meet the SPM standard for road network performance <1.50. While the ccomplishment of SPM from the aspect of mobility on route I was 0.099, route II 0.089 and on route III?0.094 ?that it show did not meet the SPM standard for road network performance <1.0. The application of SPM accomplishment from the aspect of accidents on route I 1,354, route II 1,507 and on route III 1,434 which shows that it has met the SPM standard for road network performance <2. The evaluation results of the SPM for road services have good road conditions which the SPM standard for road services of at least 60%. The evaluation results showed that on route I was 66.290%, route II was 66.292%. and on route III 66.259%. Realization of accomplishment of SPM connectivity up to 2018 47.62%, so the need for realization of accomplishment of regional connectivity SPM until 2019 can be achieved 100%.